Closing The Loop: Circular Economy Approach to Waste Management in Banten Province - Supandi, Achmad; Irmayanti, Irmayanti; Suandana, Nana; Bahtiar, Rizal; Hidayat, Topik (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
With that background, this research underscores the importance of a circular economy approach in addressing waste issues, in line with Law No. 5 of 2008 on waste management. This approach has the potential to create positive impacts on the economy, environment, and society, such as an increase in Gross Domestic Product (GDP), a reduction in waste volume, and the creation of jobs. This research aims to explore the urgency and potential of the circular economy approach in waste management in Banten Province, as well as to identify effective methods for implementing the 5R concept (Reduce, Reuse, Recycle, Recovery, and Repair) as an effort to close the waste cycle. Through an analysis of data from the Population Administration (Adminduk) and the National Waste Management Information System (SIPSN), as well as reports from The Indonesia Olefin, Aromatic & Plastic Industry Association (INAPLAS) and the Central Statistics Agency (BPS), this research notes an increase in waste volume in Indonesia, particularly plastic waste that pollutes the environment, including the sea. The proposed method to achieve this goal is the establishment of a waste bank as part of social engineering to raise public awareness about waste sorting and to utilize the economic value of waste. The waste bank is expected to serve as a collection and education point for the community in practicing the 5R concept. Additionally, the application of the 5R principles from the source of waste is also considered crucial in addressing the waste problem comprehensively and integratively. The aim of this research is to understand, identify, and analyze how the concept of "closing the loop" is applied in the circular economy model to minimize waste accumulation directly.It is hoped that this research can contribute to the understanding and implementation of the circular economy approach in waste management in Banten Province, as well as offer new perspectives in addressing the challenges faced in implementing the 5R concept.